Analysis of Foreign Direct Portfolio Investment in Nigeria - Oduntan, Kemi Olalekan (NIU Journal of Humanities, 2020)
Foreign Direct Portfolio Investment (FDPI) has grown recently in proportion relative to other types of capital inflows to Nigeria. Incidentally, there is no empirical evidence regarding the determinants of FDPI in African Countries and Nigeria in particular. Hence the paper added to knowledge by modeling the long-run impacts of foreign direct portfolio investment as well as other determinants of FDPI in Nigeria over the period 1985-2017. An Ordinary Least Square method of analysis was adopted to analyze the data sourced from the Central Bank of Nigeria (CBN) Statistical Bulletins. The study established that foreign portfolio investment, market capitalization and exchange rate have a positive long-run relationship with real gross domestic product in Nigeria. It recommended that authorities should strengthen the capital market against fraudulent activities to ensure the free flow of foreign capital into the economy. Keywords: Foreign Direct Portfolio Investment, Economic Growth, Exchange Rate, Market Capitalization